Polymers with dispersing function, polycarboxylic acid cement dispersants, their preparation and use

A polymer-based dispersant for oil well cement, composed of unsaturated polyether, unsaturated acid, and silane/siloxane structural units, addresses the limitations of current dispersants by providing high temperature resistance and excellent dispersion capacity, ensuring efficient cement slurry flowability and compatibility with other additives.

JP7660673B2Active Publication Date: 2025-04-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023522522
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-13
Filing Date
2021-08-13
Publication Date
2025-04-11
Estimated Expiration
2041-08-13

AI Technical Summary

Technical Problem

Current oil well cement dispersants, such as sulfonated aldehyde ketone polycondensate dispersants, face issues like low efficiency with complex particles, limited production due to formaldehyde use, and inability to combine with new auxiliary agents. Additionally, polycarboxylic acid-based dispersants lack high temperature resistance and compatibility with other oil well cement additives.

Method used

A polymer with a dispersion function is developed, comprising structural units derived from unsaturated polyether, unsaturated acid, and silane or siloxane with a polymerizable group. This polymer is produced through solution polymerization with a specific molar ratio and weight average molecular weight, enabling high temperature resistance and excellent dispersion capacity.

Benefits of technology

The polymer-based dispersant exhibits superior dispersibility and reduced retardation properties, maintaining high efficiency even at temperatures above 120°C. It effectively prevents cement particle aggregation, improves flowability, and blends well with other additives, making it suitable for high-temperature applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660673000013
    Figure 0007660673000013
  • Figure 0007660673000014
    Figure 0007660673000014
  • Figure 0007660673000015
    Figure 0007660673000015
Patent Text Reader

Abstract

The present invention provides a polymer with dispersing properties, a method for producing the same, and its use as a cement dispersant. The polymer contains structural units a, b, and c, where the structural unit a is derived from an unsaturated polyether, the structural unit b is derived from an unsaturated acid and / or its salt and / or its acid anhydride, and the structural unit c is derived from a silane and / or siloxane having 5 or more carbon atoms and containing a polymerizable group. The molar ratio of structural units a, b, and c is 1:(1-20):(0.01-0.5), and the weight-average molecular weight of the polymer is 20,000-90,000. Compared to conventional techniques, the polymer and dispersant of the present invention ensure high acid usage, maintaining high dispersibility, and significantly reducing the set retardation of polycarboxylic acids, particularly at temperatures above 120°C. Furthermore, the dispersant of the present invention is highly compatible with other external additives.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of Chinese patent application No. 202011092106.0, filed on October 13, 2020, the contents of which are incorporated herein by reference.

[0002] The present invention relates to the technical field of cementing, in particular to a polymer with dispersing functionality, a polycarboxylic cement dispersant, its preparation method and its use in cement cementing. [Background technology]

[0003] In the cementing operation, the cement slurry needs to be pumped into the annular space between the casing and the shaft, and the pumped cement slurry needs to have good fluidity. In actual construction, especially in the cementing of high-temperature, high-pressure, and complex wells, many additives and admixtures, such as set retarders, water loss inhibitors, density improvers, and latex materials, need to be added to the cement slurry to meet the needs of cementing, which results in poor fluidity of the slurry and makes pumping difficult. Therefore, under the condition of a certain water-cement ratio, it is often necessary to add a dispersant to the cement slurry so that the viscosity of the cement slurry can be reduced, the fluidity can be improved, and turbulent injection at a low speed can be achieved.

[0004] At present, the oil well cement slurry dispersants at home and abroad in China are mainly sulfonated aldehyde ketone polycondensate dispersants, which have been widely used in oil fields since their appearance in the 1970s. However, with the development of other auxiliary agents for oil well cement and the further improvement of environmental protection standards, the shortcomings of such dispersants have become apparent: 1. It cannot be blended with new auxiliary agents; 2. Its dispersion efficiency is low for cement slurries with the addition of complex particles (latex, rubber particles, etc.); 3. Its raw materials contain formaldehyde, and its production is currently restricted.

[0005] At present, polycarboxylic acid-based water reducers are commonly used in the construction industry, and patents for polycarboxylic acid-based water reducers are mainly held by the construction industry. In recent years, the oil well cement industry has also attempted to introduce polycarboxylic acid-based dispersants instead of sulfonated aldehyde ketone polycondensate dispersants. However, polycarboxylic acid water reducers in the construction industry cannot be directly used in the oil well cement industry due to problems with heat resistance and compatibility. There are not many patents for polycarboxylic acid-based dispersants (which are considered water reducers in the construction industry) targeted at the oil well cement industry, but this is because polycarboxylic acid-based dispersants have problems with high temperature resistance, as well as the problem that they cannot be mixed with oil well cement-specific setting retarders, water loss inhibitors, and early strength agents, which are difficult to solve. At present, polycarboxylic acid-based dispersants outside of China can generally withstand temperatures lower than 120°C, and must be used together with a specified water loss inhibitor. Therefore, in actual production, polycarboxylic acid-based dispersants that are high temperature resistant, highly efficient, environmentally friendly, and have good compatibility are expected to replace the existing sulfonated aldehyde ketone polycondensate dispersants.

[0006] CN105754045A discloses a silane coupling agent modified polycarboxylic acid water reducer and its manufacturing method, and all examples mention that the upper limit temperature for manufacturing is 45°C. The specific steps are as follows, and the parts of raw materials are parts by weight. 1) 350 parts of polyether macromonomer are placed in a reaction vessel, 5-15 parts of acrylic acid are added and stirred uniformly, and then 0.5-5 parts of double bond-containing silane coupling agent are added and stirred until a solution without obvious lumps or flakes is obtained, and the polyether macromonomer is one or more of methylallyl polyoxyethylene ether, isopentenyl alcohol polyoxyethylene ether, and modified isopentenyl alcohol polyoxyethylene ether. 2) 2.5-6 parts of oxidizing agent, 2.5-3.5 parts of initiator, and 20-37 parts of micromonomer are sequentially dropped into the solution obtained in step 1) while stirring, and the dropping time of the micromonomer solution is 1-4 hours, and the micromonomer is one or more of acrylic acid, sodium methacryloylsulfonate, 2-acrylamido-2-methylpropanesulfonic acid, itaconic acid, fumaric acid, and maleic anhydride. 3) After aging the solution of step 2) for 1-2 hours, neutralize it by adding liquid alkali, stabilize the pH at 6, and further add 1-3 parts of a silane coupling agent that does not contain a double bond and stir uniformly. The water reducer produced by this patent application does not have a high dispersing ability because the reaction temperature is not high and 2-acrylamido-2-methylpropanesulfonic acid is used as the small molecule used.

[0007] CN107245131A discloses a method for preparing a polycarboxylic acid water reducer of slump loss reduction type by silylation of amino polyether end group, and the polycarboxylic acid water reducer is prepared by hydrolysis, Williamson etherification, condensation, and copolymerization using silane coupling agent, polyether compound, unsaturated carboxylic acid monomer, etc. as main reacting raw materials, that is, halogenated silane coupling agent is hydrolyzed first, and Williamson etherification reaction occurs with polyether compound, and the etherification product is condensed with alkenyl silane coupling agent hydrolyzate, and the condensation product is radical copolymerized with unsaturated polyoxyethylene ether, molecular weight modifier, and unsaturated carboxylic acid monomer under the action of initiator to prepare a polycarboxylic acid water reducer having a plurality of silane coupling agent modified polyether side chains. However, this preparation method is complicated.

[0008] CN108250370A discloses polycarboxylic acid and its use in cement, which uses unsaturated polyether monomers, unsaturated carboxylic acid monomers, functional monomers, etc. as main reaction raw materials. Among them, 3-methacryloyloxypropyltrimethoxysilane is described as a functional monomer, and its amount is 0-5, preferably 0.5-4, in terms of molar ratio to polyester monomer. In the high-temperature use environment of oil well cement, when this preferred amount of silane-synthesized polycarboxylic acid is added to oil well cement slurry, when used at high temperatures (70-150°C, especially 120°C or higher), the setting curve will swell in setting experiments, and in severe cases, it will become unusable.

[0009] In the paper "Effect of silane-functional polycarboxylic acid water reducer on the fluidity and mechanical properties of cement slurry" (Kong Xiangming et al., Journal of Silicate Science, Vol. 42, No. 5, May 2014), a silane-modified polycarboxylic acid water reducer was synthesized by radical polymerization using KH570, acrylic acid (AA) monomer, and macromonomer HPEG, and its effect on the strength development of cement mortar was evaluated. This water reducer has poor slump retention and adaptability, and HPEG is easily altered in summer and difficult to store.

[0010] Therefore, there is a demand for dispersants that have good dispersibility and do not retard setting. Summary of the Invention [Problem to be solved by the invention]

[0011] In response to the above problems in the prior art, the present invention provides a novel oil well cement dispersant that has high temperature resistance, excellent dispersing ability, and greatly reduced set retardation, and in particular has no set retardation even at high temperatures above 120°C, and has excellent dispersing ability when used in combination with other oil well cement additives under conditions of 120-180°C, and is environmentally friendly in terms of raw materials, production, and use, and overcomes the disadvantages of sulfonated aldehyde ketone polycondensate dispersants, which have low efficiency and serious pollution, and polycarboxylic acid dispersants, which have poor heat resistance. [Means for solving the problem]

[0012] The first aspect of the present invention is A polymer having dispersing properties, The polymer comprises structural units a, b, and c, wherein the structural unit a is derived from an unsaturated polyether, the structural unit b is derived from an unsaturated acid and / or a salt thereof and / or an acid anhydride thereof, and the structural unit c is derived from a silane and / or siloxane having 5 or more carbon atoms and containing a polymerizable group, the molar ratio of the structural units a, b, and c being 1:(1-20):(0.01-0.5), and the weight average molecular weight of the polymer is 20,000-90,000.

[0013] A second aspect of the present invention is 1. A method for producing a polycarboxylic acid cement dispersant, comprising the steps of: polymerizing a monomer mixture in water in the presence of an initiator under solution polymerization conditions, The monomer mixture contains monomer A, monomer B, and monomer C, wherein monomer A is an unsaturated polyether, monomer B is an unsaturated acid and / or an acid anhydride thereof and / or a salt thereof, and monomer C is a silane and / or siloxane having 5 or more carbon atoms and containing a polymerizable group, wherein the molar ratio of monomer A, monomer B, and monomer C in the monomer mixture is 1:(1-20):(0.01-0.5), and polymerization conditions are such that the weight average molecular weight of the obtained polymer is 20,000-90,000.

[0014] A third aspect of the invention provides the use of a dispersant as defined above or prepared by the process defined above in a cement slurry for cementing. Effect of the Invention

[0015] Compared with the prior art, the polymer and dispersant of the present invention ensure high dispersibility by using a hydrophobic long-chain siloxane (e.g., carbon atom length of 5 to 25) to ensure a high acid usage amount, and also significantly reduce the setting retardation of polycarboxylic acid, and in particular, there is no setting retardation even at high temperatures above 120°C. Furthermore, the dispersant of the present invention has excellent compatibility with other external additives. [Brief description of the drawings]

[0016] [Figure 1] FIG. 2 is a gel chromatography analysis diagram of the polymer produced in Example 1. [Diagram 2] 1 is an infrared spectrum of the polymer produced in Example 1. [Diagram 3] 1 is a nuclear magnetic resonance hydrogen spectrum of the polymer produced in Example 1. [Figure 4] FIG. 2 is a thermogravimetric analysis diagram of the polymer produced in Example 1. [Diagram 5] 1 is a DSC spectrum of the polymer produced in Example 1. [Figure 6] 1 is a linear chart showing the viscosity increase at 150° C. in the cement slurry of Table 3 for the dispersant produced in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The range endpoints and any values ​​disclosed herein are not limited to the exact ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. In the case of numerical ranges, the values ​​between the endpoints of each range, between the endpoints of each range and the individual point values, and between the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.

[0018] The first aspect of the present invention is A polymer having dispersing properties, The polymer comprises structural units a, b, and c, wherein the structural unit a is derived from an unsaturated polyether, the structural unit b is derived from an unsaturated acid and / or a salt thereof and / or an acid anhydride thereof, and the structural unit c is derived from a silane and / or siloxane having 5 or more carbon atoms and containing a polymerizable group, the molar ratio of the structural units a, b, and c being 1:(1-20):(0.01-0.5), and the weight average molecular weight of the polymer is 20,000-90,000.

[0019] In the present invention, the polymerizable group may be one or more of various groups capable of undergoing a bonding reaction with other monomers under certain conditions, such as a carbon-carbon double bond, a carbon-carbon triple bond, and an epoxy group.

[0020] Preferably, the silane and / or siloxane has a structure according to formula (I). [ka] (In formula (I), R1, R2, R3, R1', and R2' are each independently selected from H and an alkyl group having C1 to C4; R a , R b and R care each independently selected from H, a C1 to C4 alkyl group or an alkoxy group, and n is an integer of 5 to 25, preferably an integer of 8 to 18.

[0021] The silanes and / or siloxanes used in the present invention are silanes or siloxanes containing unsaturated double bonds and having 7 or more carbon atoms, where n can be 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, or 25.

[0022] In the present invention, the C1-C4 alkyl group may be a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, or a t-butyl group.

[0023] In the present invention, the C1-C4 alkoxy group may be a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, an isobutoxy group, or a t-butoxy group.

[0024] The silanes and / or siloxanes used in the present invention include, for example, vinyloctadecyltrimethoxysilane (i.e., in formula (I), n is 18, same as below), vinylhexadecyltrimethoxysilane, vinyltetradecyltrimethoxysilane, vinyldodecyltrimethoxysilane, vinyldecyldimethoxysilane, vinyloctyldimethoxysilane, 7-octenyltrimethoxysilane, vinylhexyldimethoxysilane, vinyloctadecyldimethoxysilane, vinylhexadecyldimethoxysilane, vinyltetradecyldimethoxysilane, , vinyl dodecyl dimethoxy silane, vinyl decyl dimethoxy silane, vinyl octyl dimethoxy silane, vinyl hexyl dimethoxy silane, vinyl octadecyl trimethyl silane, vinyl hexadecyl trimethyl silane, vinyl tetradecyl trimethyl silane, vinyl dodecyl trimethyl silane, vinyl decyl trimethyl silane, vinyl octyl trimethyl silane, vinyl hexyl trimethyl silane, vinyl octadecyl dimethyl silane, vinyl hexadecyl dimethyl silane, vinyl tetradecyl dimethyl silane, vinyl vinyl dodecyl dimethyl silane, vinyl decyl dimethyl silane, vinyl octyl dimethyl silane, vinyl hexyl dimethyl silane, propenyl octadecyl trimethoxy silane, propenyl hexadecyl trimethoxy silane, propenyl tetradecyl trimethoxy silane, propenyl dodecyl trimethoxy silane, propenyl decyl dimethoxy silane, propenyl octyl dimethoxy silane, propenyl hexyl dimethoxy silane, propenyl octadecyl dimethoxy silane, propenyl hexadecyl dimethoxy silane, propenyl tetradecyl dimethoxy silane Methoxysilane, propenyldodecyldimethoxysilane, propenyldecyldimethoxysilane, propenyloctyldimethoxysilane, propenylhexyldimethoxysilane, propenyloctadecyltrimethylsilane, propenylhexadecyltrimethylsilane, propenyltetradecyltrimethylsilane, propenyldodecyltrimethylsilane, propenyldecyltrimethylsilane, propenyloctyltrimethylsilane, propenylhexyltrimethylsilane, propenyloctadecyldimethylsilane, propenylhexadecyldimethylsilane,The silane may be one or more of propenyltetradecyldimethylsilane, propenyldodecyldimethylsilane, propenyldecyldimethylsilane, propenyloctyldimethylsilane, and propenylhexyldimethylsilane.

[0025] In the present invention, the structural unit a is derived from an unsaturated polyether, which means that the structural unit a is formed by opening the double bond of an unsaturated polyether and polymerizing it. The rest is the same.

[0026] In the present invention, the weight average molecular weight of the polymer is preferably from 25000 to 55000. The weight average molecular weight is measured by a GPC method.

[0027] According to some embodiments of the present invention, the molar ratio of the structural unit a, the structural unit b and the structural unit c is 1:(4 to 12)(0.05 to 0.3).

[0028] In the polymer of the present invention, the amount of silane and / or siloxane used is small, so that crosslinking of silyl groups or siloxy groups that may occur when a large amount is used is effectively avoided. As a result, when the polymer of the present invention is used as a cement dispersant, thickening of the cement slurry can be effectively prevented.

[0029] In the present invention, the presence and molar contents of the structural units a, b and c are determined by infrared spectroscopy. 1 It can be measured by a combination of H-NMR methods.

[0030] According to some embodiments of the present invention, the polymer has a comb-like structure, which is a structure in which carbon-carbon double bonds are polymerized to form a backbone structure, and each structural unit is linked to a carbon-carbon double bond to form a pendant structure resembling the teeth of a comb.

[0031] According to some embodiments of the present invention, the polymer is a random copolymer. The fact that the polymer of the present invention is a random copolymer can be confirmed by a single peak in the DSC of the polymer.

[0032] According to some embodiments of the invention, the unsaturated polyether has a structure represented by formula (2): [ka] (In formula (2), E represents an alkylene group having 2 to 4 carbon atoms, such as an ethylene group -CHCH-, -CHCHCHCH-, -CHCHCHCHCH-, -CHCHCH(CH)-, -CHC(CH)-, or -CH(CH)CH(CH)-; F represents an alkylene group having 2 to 4 carbon atoms other than E; R 4 and R 5 each independently represents H or an alkyl group having 1 to 5 carbon atoms, preferably a methyl group; R 6 represents a C1-C4 alkyl group, Y represents an alkylene group having 1 to 5 carbon atoms; p represents an integer of 0 to 200, preferably 20 to 140; q represents an integer of 0 to 200, preferably 20 to 140; p+q>10, preferably p+q≧40.

[0033] In the present invention, the alkyl group having 1 to 5 carbon atoms may be a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a t-butyl group, or a pentyl group.

[0034] According to some embodiments of the present invention, the unsaturated polyether is at least one selected from methylallyl polyoxyethylene ether (HPEG), methylallyl polyoxypropylene ether, isopentenyl polyoxyethylene ether (TPEG), and isobutenyl polyoxyethylene ether.

[0035] According to some embodiments of the present invention, the unsaturated carboxylic acid has a structure represented by formula (II): [ka] In formula (II), R1, R2 and R3 are each independently selected from hydrogen, a C1-C6 alkyl group and -COOH, and X is (CH2) n and n is 0, 1, 2, 3, 4, 5, or 6.

[0036] According to some embodiments of the present invention, the "unsaturated acid or its salt or its anhydride" refers to an unsaturated acid, or a sodium salt, potassium salt, or ammonium salt of an unsaturated acid, or an anhydride of an unsaturated acid. Preferably, the unsaturated acid is at least one selected from acrylic acid, methacrylic acid, vinyl sulfonic acid, vinyl phosphoric acid, maleic acid, itaconic acid, fumaric acid, 2-acrylamido-2-methylpropanesulfonic acid, styrenesulfonic acid, and propenylsulfonic acid.

[0037] In the present invention, the content of each structural unit in the polymer and the structural characteristics of the polymer may be measured by conventional methods in the prior art, and the characterization is carried out, for example, by infrared spectroscopy, nuclear magnetism, gel chromatography, TGA-DSC, etc. Specifically, for example, in infrared spectroscopy, -1 and 1110cm -1 corresponds to -OH and -COC- of unsaturated polyether monomers (e.g., TPEG), and 2882 cm -1 corresponds to -CH3, 1593 cm -1 corresponds to -COO- of unsaturated acids (e.g. acrylic acid), and 1465cm -1 and 2882 cm -1 corresponds to -CH2- in the long chain of long linear silanes and / or siloxanes, and 1347 cm -1 corresponds to -Si-C-, and 1100 cm -1 corresponds to -CO- or -Si-O-, and 1645 to 1620 cm -1 The absence of an absorption peak between indicates that no "-C=C-" remains. The area of ​​the peak at each position in the hydrogen nuclear magnetic spectrum allows quantification of the content of each structural unit and the number of -CH2- in the long chain of the long linear silane and / or siloxane.

[0038] In thermogravimetric (TGA) analysis, the temperature corresponding to the peak represents the thermal stability of the polymer.

[0039] The molecular weight and distribution of the polymer are measured by gel permeation chromatography (GPC) analysis.

[0040] The above polymer can function as a cement dispersant, and the performance of the cement slurry is best achieved by adjusting the amount of dispersant used. The polycarboxylic acid cement dispersant has a viscosity index of 1.5 or less, preferably 1 to 1.35, at a temperature of 120°C or higher, a compressive strength index of 0.8 or more, preferably 0.95 to 1.1, more preferably 1.0 to 1.1 at 110°C and 24h, a consistency coefficient of 0.8 or less, preferably 0.4 to 0.75, and a liquid index n of 0.6 or more, preferably 0.7 to 0.95 at 85°C. When used as a cement dispersant, the polymer according to the present invention not only has controllable setting retardation and compatibility with other additives at 120°C, but also has excellent setting retardation controllability and a short thickening time at higher temperatures, and is particularly suitable for high-temperature working environments, since the viscosity index at 150°C can reach 0.95 to 1.5, preferably 0.98 to 1.2, for example.

[0041] In the present invention, the thickening index is the ratio of the thickening time of the cement paste after adding the cement dispersant to that of the cement paste before adding the cement dispersant, where the cement paste may be a slurry obtained by mixing various cements for cementing with water.

[0042] In the present invention, the thickening time, consistency coefficient K, liquid index n and compressive strength are all measured according to GB / T 19139-2003 standard.

[0043] As is evident from the above data, the polymers according to the present invention, when used as polycarboxylic cement dispersants, have almost no set retardation at high temperatures, and therefore can meet the needs of various applications, such as cementing, general construction, and other cement applications that may or may not require set retardation.

[0044] Preferably, the polymer content is 10-90% by weight, preferably 20-40% by weight, based on the total amount of the polycarboxylic acid cement dispersant, where the total amount of the polycarboxylic acid cement dispersant includes the amount of the solvent used in the polymerization reaction.

[0045] Preferably, the polymer content is 90% by weight or more, preferably 95% by weight or more, based on the solid content of the polycarboxylic acid cement dispersant.

[0046] A second aspect of the present invention provides a method for producing a dispersant, the method comprising the step of polymerizing a monomer mixture in water in the presence of an initiator under solution polymerization conditions, the monomer mixture containing monomer A, monomer B and monomer C, the monomer A being an unsaturated polyether, the monomer B being an unsaturated acid and the monomer C being a silane and / or siloxane having 5 or more carbon atoms and containing a polymerizable group, the molar ratio of the monomer A, monomer B and monomer C being 1:(1-20):(0.01-0.5) in the monomer mixture, and the polymerization conditions being such that the weight average molecular weight of the obtained polymer is 20,000-90,000, preferably 25,000-55,000.

[0047] The molar ratio of the monomer A, the monomer B and the monomer C is 1:(4-12):(0.05-0.3).

[0048] Monomer A, Monomer B and Monomer C have been described above and will not be described in detail here.

[0049] In the present invention, said silane coupling agent can be produced by referring to the conventional method in this field, for example, first, the Grignard reagent having the structure represented by formula (I') is reacted with tetrachlorosilane to obtain long-chain chlorosilane, and then the obtained long-chain chlorosilane is alcoholyzed to obtain the silane coupling agent of the present invention.Here, the production conditions of silane coupling agent are not particularly limited, and it is sufficient to meet the needs of the present invention. [ka] In formula (I'), R1, R2, R3, R1', R2', R a , R b , R c and n are the same as those in formula (I). Alternatively, it can be obtained by reacting a long-chain chlorosilane with a Grignard reagent (hydrocarbon-based magnesium halide (R-MgX)), e.g., Cl(CH2) 16 SiH(CH3)2+H2C=CH-CH2MgCl → H2C=CH-CH2-(CH2) 16 The corresponding long-chain silanes are obtained by the reaction of SiH(CH3)2 + MgCl2.

[0050] The long-chain silane may be self-prepared, but the specific reaction conditions are well known to those skilled in the art and will not be described in detail here. Unless otherwise specified, the silane coupling agents used in the embodiments of the present invention are prepared by the above-mentioned known methods.

[0051] According to some embodiments of the present invention, the polymerization reaction conditions include a temperature of 40-80° C., preferably 50-70° C., and a time of 1-10 hours, preferably 2-8 hours.

[0052] According to some embodiments of the present invention, the initiator is at least one selected from oxydol-ascorbic acid (oxidizing agent-reducing agent), sodium hydrogen sulfite, sodium formaldehyde sulfoxylate, and sodium dithionite, and the oxidizing agent is at least one selected from oxydol, peracetic acid, ammonium persulfate, sodium persulfate, and potassium persulfate. Preferably, the concentration of the oxydol is 25 to 35% by weight.

[0053] According to some embodiments of the present invention, the content of the initiator is 0.01 to 2% by weight, preferably 0.1 to 1% by weight, of the total amount of the monomer mixture.

[0054] According to some embodiments of the present invention, the polymerization reaction is carried out in the presence of a chain transfer agent. The amount of the chain transfer agent is not particularly limited as long as it satisfies the needs of the present invention. For example, the content of the chain transfer agent is 0.01-2 wt% of the total amount of the monomer mixture.

[0055] According to the present invention, the chain transfer agent is selected from thioglycolic acid and / or 3-mercaptopropionic acid.

[0056] In the present invention, the polymerized material (containing solvent) can be directly used as a cement slurry dispersant without further post-treatment after the polymerization reaction, however, the polymer may be subjected to corresponding purification treatment according to the characterization requirements when characterizing the relevant structures.

[0057] According to a preferred embodiment of the present invention, in order to prevent self-polymerization and explosive polymerization and make the comb-like structure more uniform and regular, the specific operation of the method of the present invention includes simultaneously dropping a solution containing an oxidizing agent, a solution containing an unsaturated acid or its salt or its acid anhydride, a silane coupling agent (a silane and / or siloxane having 5 or more carbon atoms and containing a polymerizable group), a solution containing an initiator and a chain transfer agent into a solution of an unsaturated polyether, and carrying out a polymerization reaction under polymerization conditions.

[0058] In the present invention, when the dropping method is adopted, the above polymerization reaction time includes the dropping time, that is, the polymerization reaction time is calculated from the start of dropping. Preferably, in order to carry out the polymerization more thoroughly, after the dropping of the material is completed, the heat-retention reaction is continued for 0.5 to 1.5 hours.

[0059] According to some embodiments of the present invention, the drop time of the solution containing an unsaturated acid and / or a salt thereof and / or an acid anhydride thereof is 2 to 4 hours, the drop time of the solution of the silane coupling agent and the unsaturated polyether is 2 to 4 hours, and the drop time of the solution containing an initiator and a chain transfer agent and the solution of the unsaturated polyether is 2.5 to 4.5 hours.

[0060] In the present invention, the concentration of the oxidizing agent in the solution containing the oxidizing agent is 9 to 40% by weight.

[0061] In the present invention, in a solution containing an unsaturated acid and / or a salt thereof and / or an acid anhydride thereof, the total concentration of the solution of the unsaturated acid and / or a salt thereof and the acid anhydride is 2 to 80% by weight.

[0062] In the present invention, in the solution containing the initiator and the chain transfer agent, the concentration of the initiator is 1 to 10% by weight, and the concentration of the chain transfer agent is 1 to 10% by weight, preferably 2 to 6% by weight.

[0063] In the present invention, the concentration of the unsaturated polyether in the solution is 10 to 60% by weight.

[0064] In the present invention, the solvent in the solution containing an oxidizing agent, the solution containing an unsaturated acid and / or a salt thereof and / or an acid anhydride thereof, the solution containing an initiator and a chain transfer agent, and the solution of an unsaturated polyether monomer may be water.

[0065] According to a more preferred embodiment of the invention, the method further comprises the steps of: (1) adding unsaturated polyether and deionized water to a reaction vessel and thoroughly stirring until homogeneous; (2) Starting with heating, when the temperature is raised to 50 to 70°C, a step of keeping the temperature until the reaction is completed; (3) adding an oxidizing agent or an initiator to deionized water, stirring uniformly, and then adding the mixture to a reaction vessel; (4) preparing a mixed aqueous solution of a reducing agent or initiator and a chain transfer agent, the reducing agent or initiator and the chain transfer agent being added to deionized water and thoroughly stirred to dissolve; (5) preparing an aqueous solution of an unsaturated acid and / or its salt and / or its anhydride, comprising adding the unsaturated acid and / or its salt and / or its anhydride to deionized water and dissolving the unsaturated acid and / or its salt and / or its anhydride by sufficient stirring; (6) simultaneously dropping an aqueous solution of an unsaturated acid and / or its salt or and / or its acid anhydride, a silane and / or a siloxane, and an aqueous solution of a mixture of an initiator and a chain transfer agent, dropping the first two materials for 2-4 hours, and dropping the aqueous solution of a mixture of an initiator and a chain transfer agent for 2.5-4.5 hours; (7) After the dropping is completed, the mixture is kept warm and stirred for another 0.5 to 1 hour, cooled, and the material is discharged.

[0066] The present invention further provides an oil well cement dispersant produced by the above-mentioned production method. As described above, the dispersant according to the present invention has excellent dispersibility and low set retardation, and can be used in various situations by blending with other auxiliaries to achieve various purposes.

[0067] In the present invention, the amount of the dispersant used is preferably 0.1 to 5% by weight of the cement slurry.

[0068] Effect of the Invention The beneficial effects of the present invention are at least as follows: 1. The dispersing polymer of the present invention contains long-chain silane or siloxane structural units, so that it can increase anchor sites and reduce the setting retardation caused by the same amount of carboxylic acid adsorption, and therefore, when used as a dispersing agent, it has excellent dispersibility and greatly reduced setting retardation compared with dispersing agents that simply use carboxylic acid groups as adsorption groups, and has the advantage of being more reduced setting retardation and no setting retardation compared with general short-chain silane coupling agents with less than 5 carbon atoms, and can be easily mixed with other auxiliaries such as water loss inhibitors and setting retarders. The dispersing agent can effectively prevent the aggregation of cement particles and improve the fluidity of cement slurry, and the application temperature can reach up to 150°C. 2. The dispersant of the present invention has a polyether macromonomer skeleton, and the resulting polycarboxylic acid dispersant has a comb structure, which significantly improves the dispersion efficiency and can withstand higher temperatures than polyester. 3. The polymer of the present invention can have a higher carboxylic acid content, so that when used as a dispersant, it can greatly improve the dispersion efficiency. The hydrophobic long chain reduces the integrity of the hydration film on the surface of cement particles, thereby reducing the set retardation. Compared with the previous invention, which reduces the set retardation caused by carboxylic acid by using 2-acrylamido-2-methylpropanesulfonic acid as a partial replacement for carboxylic acid, the present invention uses a different technical concept to solve the problem of the contradiction between the dispersion efficiency and set retardation caused by carboxylic acid. 4. Experimental results show that the dispersant of the present invention has lower retardation or even no retardation at high temperatures. For example, the difference between the thickening time at 150°C and the thickening time at 120°C is smaller than that of the paste itself. Therefore, the dispersant of the present invention can be used in high temperature environments, and has lower retardation at high temperatures and is more effective.

[0069] In order to facilitate understanding of the present invention, the present invention will be described in detail below with reference to examples. However, these examples only serve to explain the present invention and are not intended to limit the scope of the present invention.

[0070] All the raw materials used in the present invention are commercially available. EXAMPLES

[0071] In the following examples and comparative examples, the content of each structural unit in the polymer is determined by the amount of monomer input, specifically, the input ratio of each monomer actually involved in polymerization is determined by measuring the content of unreacted monomer, and the content of each structural unit in the polymer is determined, and the solid content is calculated from the input amount, that is, solid content = input amount excluding solvent (weight) / input amount including solvent (weight) * 100%.In the examples, since only a single peak appears in the DSC spectrum of the polymer, it is clear that all the polymers are random copolymers.

[0072] Example 1 100g (0.0417mol) of TPEG 2400 and 150g of deionized water were added to a round-bottom flask, stirred and heated to 70℃. 1.5g of oxydol was added to 15g of deionized water, stirred uniformly and added to the reaction kettle. 0.7g of ascorbic acid and 1g of 3-mercaptopropionic acid were added to 17g of deionized water to prepare a mixed aqueous solution of initiator and chain transfer agent. 37g of acrylic acid (AA) was added to 40g of deionized water to prepare an aqueous solution of acrylic acid. The mixed aqueous solution of initiator and chain transfer agent, 5g of vinyloctadecyldimethylsilane, and the aqueous solution of acrylic acid were simultaneously added to the round-bottom flask, and the dropping of the aqueous solution of acrylic acid and vinyloctadecyldimethylsilane was completed over 4 hours under the control of a peristaltic pump, and the dropping of the mixed aqueous solution of initiator and chain transfer agent was completed over 4.5 hours. After the dropping of all the materials was completed, the mixture was kept warm and stirred for another 0.5 hours to prepare a high-temperature polycarboxylic acid oil well cement dispersant sample S1 with an actual solid content of 39.8 wt %. Structural characterization was performed on sample S1, where the purified sample was used for nuclear magnetic spectroscopy. Gel chromatography analysis (Figure 1): The weight average molecular weight of the polymer is 35,000. Infrared spectroscopy (Figure 2): Polyether TPEG: 3442 cm -1and 1110cm -1 corresponds to -OH and -COC-, and 2882 cm -1 corresponds to -CH3, acrylic acid: 1593cm -1 corresponds to -COO-, long chain silane: 1461cm -1 and 2882 cm -1 corresponds to the long linear -CH2-, 1347cm -1 corresponds to -Si-C-, and 1100 cm -1 corresponds to -COC- or -Si-O-Si-, and no double bond remains, i.e., 1645-1620 cm -1 There is no -C=C- between them. Nuclear magnetic hydrogen spectrum (Figure 3): At 0 ppm, the characteristic proton absorption peak corresponds to siloxane, at 0.74 ppm to the side chain end group -CH3, at 1.20 ppm to -CH2- of long chain silane, at 1.62 ppm and 2.26 ppm to the methyl and methine groups of AA, respectively, at 3.73 ppm to -CH2-CH2-O- in TPEG, and at 4.69 ppm to the water peak. Thermogravimetric analysis (Figure 4): An absorption peak appears only at 295°C, indicating excellent high temperature resistance. In the DSC spectrum, a single peak appears at 49.22° C., which indicates that the polymer is a random copolymer.

[0073] Example 2 100g of TPEG1500 and 160g of deionized water were added to a round-bottom flask, stirred and heated to 50°C. 0.5g of oxydol was added to 5g of deionized water, stirred uniformly and added to the reaction kettle. 0.25g of ascorbic acid and 0.2g of 3-mercaptopropionic acid were added to 5.5g of deionized water to prepare a mixed aqueous solution of initiator and chain transfer agent. 34.6g of itaconic acid (IA) was added to 34g of deionized water to prepare an itaconic acid aqueous solution. The mixed aqueous solution of initiator and chain transfer agent, 0.85g of vinyloctyltrimethoxysilane, and the itaconic acid aqueous solution were simultaneously dropped into a round-bottom flask, respectively, and controlled by a peristaltic pump. The dropping time of the itaconic acid aqueous solution and vinyloctyltrimethoxysilane was 2 hours, and the dropping time of the mixed aqueous solution of initiator and chain transfer agent was 2.5 hours. After the dripping of all the materials was completed, the mixture was kept warm and stirred for another hour to prepare high-temperature polycarboxylic acid oil well cement dispersant sample S2 with an actual solid content of 39.7% by weight. The weight-average molecular weight of the polymer was 29340 as measured by gel chromatography.

[0074] Example 3 100g (0.025mol) of HPEG 4000 and 140g of deionized water were added to a round-bottom flask, stirred and heated to 65℃. 0.9g of oxydol was added to 4.5g of deionized water, stirred uniformly and added to the reaction kettle. 0.35g of ascorbic acid and 0.8g of 3-mercaptopropionic acid were added to 11g of deionized water to prepare a mixed aqueous solution of initiator and chain transfer agent. 14.4g of acrylic acid (AA) was added to 22g of deionized water to prepare an aqueous solution of acrylic acid. The mixed aqueous solution of initiator and chain transfer agent, 1.85g of vinyloctadecyldimethylmethoxysilane, and the aqueous solution of acrylic acid were simultaneously added to the round-bottom flask, and the dropping time of the aqueous solution of acrylic acid and vinyloctadecyldimethylmethoxysilane was 3 hours, and the dropping time of the mixed aqueous solution of initiator and chain transfer agent was 3.5 hours, controlled by a peristaltic pump. After the dripping of all the materials was completed, the mixture was kept warm and stirred for another hour to prepare high-temperature polycarboxylic acid oil well cement dispersant sample S3 with an actual solid content of 39.6% by weight. The weight-average molecular weight of the polymer was 31090 as measured by gel chromatography.

[0075] Example 4 The method of Example 1 was followed, except that instead of adding 37 g of acrylic acid (AA) to 40 g of deionized water, 3 g of acrylic acid (AA) was added to 74 g of deionized water to prepare an acrylic acid solution. Oil well cement dispersant sample S4 was prepared with an actual solids content of 39.8 wt. %. The weight average molecular weight of the polymer was 34222 as determined by gel chromatography.

[0076] Example 5 The method of Example 1 was followed, except that instead of adding 37 g of acrylic acid (AA) to 40 g of deionized water, 62 g of acrylic acid (AA) was added to 15 g of deionized water to prepare the acrylic acid solution. Oil well cement dispersant sample S5 was prepared with an actual solids content of 39.8 wt. %. The weight average molecular weight of the polymer was 36143 as determined by gel chromatography.

[0077] Example 6 The procedure of Example 3 was followed, except that vinyloctadecyldimethylmethoxysilane was replaced with an equimolar amount of 7-octenyltrimethoxysilane. Sample S6 of oil well cement dispersant was prepared with an actual solid content of 39.6% by weight. The weight average molecular weight of the polymer was 33412 as measured by gel chromatography.

[0078] Example 7 The procedure of Example 3 was followed, except that the amount of vinyloctadecyldimethylmethoxysilane used was 0.2 g. Sample S7 of oil well cement dispersant was prepared with an actual solid content of 39.5 wt %. The weight average molecular weight of the polymer was 35898 as measured by gel chromatography.

[0079] Comparative Example 1 The procedure of Example 3 was followed, except that an equimolar amount of KH-570 was used instead of vinyloctadecyldimethylmethoxysilane. An oil well cement dispersant comparison sample D1 was prepared with an actual solid content of 39.8% by weight. The weight average molecular weight of the polymer was 32347 as measured by gel chromatography.

[0080] Measurement example The cement slurry was prepared according to GB / T 19139-2003 standard, and the rheological performance, stability, thickening time and compressive strength were evaluated. The technical indexes are shown in Table 1. The results of the samples of Examples 1-7 and Comparative Examples 1-2 for different paste systems are shown in Table 2, Table 3 (the mixing amount of dispersant is 0.5% of the mass of cement in each case, and the thickening linear chart of the polymer prepared in Example 1 at 150℃ in the cement slurry in Table 3 is shown in Figure 6) and Table 4. Here, in order to demonstrate that the dispersant of the present invention solves the defect of polycarboxylic acid-based dispersant in delaying setting at high temperature, the measurement temperatures are 120℃ and 150℃ when comparing the thickening time. The cement used is G-grade cement manufactured by Sichuan Jiahua Co., Ltd., the water loss inhibitor and the set retarder are purchased from China Petrochemical Engineering Technology Research Institute, SCF-180L water loss inhibitor and SCR-3 set retarder, where the water loss inhibitor is a 2-acrylamido-2-methylpropanesulfonic acid (AMPS)-based water loss inhibitor, the set retarder is an acid-based set retarder, and the comparative dispersant (Comparative Example 2) is a dispersant purchased from BASF of Germany, which is a polycarboxylic acid-based dispersant. The composition of paste 1 is 100 parts by weight of cement + 44 parts by weight of water, the composition of paste 2 is 100 parts by weight of cement + 4 parts by weight of water loss inhibitor + 40 parts by weight of water, and the composition of paste 3 is 450g of cement + 225g of silicon powder + 225g of manganese powder (density enhancing material) + 31.5g of water loss inhibitor + 27g of nano liquid silicon + 27g of latex + 14g of setting retarder + 2.3g of dispersant + 200g of on-site water. The liquid index n of the cement slurry represents the rheological performance of the cement slurry, and the larger n, the better the fluidity. The consistency coefficient K represents the viscosity of the fluid, and the larger K, the higher the viscosity and the worse the fluidity. The thickening index represents the ratio of the thickening time (min) of the cement slurry with added dispersant to the thickening time (min) of the blank cement slurry without added dispersant.

[0081] [Table 1]

[0082] [Table 2]

[0083] [Table 3]

[0084] [Table 4]

[0085] From the evaluation results in Tables 2, 3 and 4, it can be seen that the dispersant according to the present invention has excellent dispersibility, does not cause setting delay when the temperature exceeds 120°C, and is excellent in compatibility with water loss inhibitors, setting retarders, etc.

[0086] The above are only preferred examples of the present invention. Those skilled in the art can make other equivalent modifications and improvements based on the technical teachings of the present invention and the common knowledge in this field, which should also be considered as within the patent scope of the present invention.

Claims

1. A polymer having dispersing properties, The polymerizable composition according to the present invention comprises a structural unit a, a structural unit b, and a structural unit c, the structural unit a being derived from an unsaturated polyether, the structural unit b being derived from an unsaturated acid and / or a salt thereof and / or an acid anhydride thereof, the structural unit c being derived from a silane and / or a siloxane having 5 or more carbon atoms and containing a polymerizable group, the molar ratio of the structural unit a, the structural unit b, and the structural unit c being 1:(1 to 20):(0.01 to 0.5), The weight average molecular weight of the polymer is 20,000 to 90,000; The unsaturated polyether is a polymer having a structure represented by formula (2). 【Chemistry 1】 (In formula (2), E represents an alkylene group having 2 to 4 carbon atoms; F represents an alkylene group having 2 to 4 carbon atoms other than E; R 4 and R 5 each independently represents H or an alkyl group having 1 to 5 carbon atoms, R 6 represents an alkyl group having 1 to 4 carbon atoms, Y represents an alkylene group having 1 to 5 carbon atoms; p represents an integer of 0 to 200; q represents an integer of 0 to 200; p+q>10.)

2. The polymer according to claim 1, wherein the molar ratio of the structural units a, b and c is 1:(4-12):(0.05-0.3), and the weight average molecular weight of the polymer is 25,000-55,000.

3. 3. The polymer according to claim 1, wherein the polymerizable group is one or more of a carbon-carbon double bond, a carbon-carbon triple bond, and an epoxy group.

4. A polymer described in claim 1 or 2, wherein the structural unit c has a structure represented by formula (I). 【Chemistry 2】 (In formula (I), R 1 , R 2 , R 3 , R 1 ', and R 2 ' are each independently selected from H and an alkyl group having 1 to 4 carbon atoms; R a , R b , and R c are each independently selected from H, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group; and n is an integer from 5 to 25.)

5. The polymer described in claim 4, wherein in formula (I), R 1 , R 2 , R 3 , R 1 ', and R 2 ' are each independently selected from H and a C1 to C2 alkyl group, R a , R b and R c are each independently selected from H, a methyl group, an ethyl group, a methoxy group and an ethoxy group, and n is an integer from 8 to 18.

6. The polymer according to any one of claims 1 to 5, wherein the silane and / or siloxane is at least one of 7-octenyltrimethoxysilane, vinyldodecyltrimethoxysilane, vinylhexadecyltrimethoxysilane, and vinyloctadecyltrimethoxysilane.

7. The polymer according to any one of claims 1 to 6, which has a comb-like structure.

8. A polymer described in any one of claims 1 to 6, which is a random copolymer and has a single DSC peak.

9. In formula (2), R 4 and R 5 The polymer according to any one of claims 1 to 8, wherein p represents an integer of 20 to 140, q represents an integer of 20 to 140, and p+q≧40.

10. The polymer described in claim 9, wherein the unsaturated polyether is at least one selected from methylallyl polyoxyethylene ether, methylallyl polyoxypropylene ether, isopentenyl polyoxyethylene ether and isobutenyl polyoxyethylene ether.

11. The polymer according to any one of claims 1 to 10, wherein the unsaturated acid is at least one selected from the group consisting of acrylic acid, methacrylic acid, vinyl sulfonic acid, vinyl phosphoric acid, maleic acid, itaconic acid, fumaric acid, 2-acrylamido-2-methylpropanesulfonic acid, styrenesulfonic acid, and propenylsulfonic acid.

12. The polymer according to any one of claims 1 to 11 is contained, and the content of the polymer is 10 to 90% by weight based on the total amount of the polycarboxylic acid cement dispersant, A polycarboxylic acid cement dispersant having a thickening index of 1.5 or less at a temperature of 120°C or higher, a compressive strength index of 0.8 or more at 110°C for 24 hours, a consistency coefficient of 0.8 or less at 85°C, and a liquid index n of 0.6 or more at 85°C.

13. A polycarboxylic acid cement dispersant as described in claim 12, which has a thickening index at a temperature of 120°C or higher of 1 to 1.35, a compressive strength index at 110°C for 24 hours of 0.95 to 1.1, a consistency coefficient at 85°C of 0.4 to 0.75, and a liquid index n at 85°C of 0.7 to 0.

95.

14. 14. The polycarboxylic acid cement dispersant according to claim 12 or 13, having a thickening index at 150° C. of 0.95 to 1.

5.

15. The polycarboxylic acid cement dispersant according to claim 14, having a thickening index at 150°C of 0.98 to 1.

2.

16. The polycarboxylate cement dispersant according to claim 12, wherein the polymer content is 20 to 40% by weight based on the total amount of the polycarboxylate cement dispersant.

17. 1. A method for producing a polycarboxylic acid cement dispersant, comprising the steps of: polymerizing a monomer mixture in water in the presence of an initiator under solution polymerization conditions, the monomer mixture contains monomer A, monomer B, and monomer C, the monomer A is an unsaturated polyether, the monomer B is an unsaturated acid and / or an acid anhydride thereof and / or a salt thereof, the monomer C is a silane and / or a siloxane having 5 or more carbon atoms and containing a polymerizable group, the molar ratio of the monomer A, the monomer B, and the monomer C in the monomer mixture is 1:(1-20):(0.01-0.5), and the polymerization conditions are such that the weight average molecular weight of the obtained polymer is 20,000-90,000, The method for producing the present invention is characterized in that the unsaturated polyether has a structure represented by formula (2). 【Chemistry 3】 (In formula (2), E represents an alkylene group having 2 to 4 carbon atoms; F represents an alkylene group having 2 to 4 carbon atoms other than E; R 4 and R 5 each independently represents H or an alkyl group having 1 to 5 carbon atoms, R 6 represents an alkyl group having 1 to 4 carbon atoms, Y represents an alkylene group having 1 to 5 carbon atoms; p represents an integer of 0 to 200; q represents an integer of 0 to 200; p+q>10.)

18. The method of claim 17, wherein the polymerizable group is one or more of a carbon-carbon double bond, a carbon-carbon triple bond, and an epoxy group.

19. The method of claim 18, wherein the silane coupling agent has a structure represented by formula (I): 【Chemistry 4】 (In formula (I), R 1 , R 2 , R 3 , R 1 ', and R 2 ' are each independently selected from H and an alkyl group having 1 to 4 carbon atoms; R a , R b , and R c are each independently selected from H, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group; and n is an integer from 5 to 25.)

20. The method according to any one of claims 17 to 19, wherein the molar ratio of monomer A, monomer B and monomer C is 1:(4-12):(0.05-0.3).

21. In formula (2), R 4 and R 5 The method according to any one of claims 17 to 20, wherein p represents an integer of 20 to 140, q represents an integer of 20 to 140, and p+q≧40.

22. The method according to claim 21, wherein the unsaturated polyether is at least one selected from methylallyl polyoxyethylene ether, methylallyl polyoxypropylene ether, isopentenyl polyoxyethylene ether and isobutenyl polyoxyethylene ether.

23. The method according to any one of claims 17 to 22, wherein the unsaturated acid is at least one selected from the group consisting of acrylic acid, methacrylic acid, vinyl sulfonic acid, vinyl phosphoric acid, maleic acid, itaconic acid, fumaric acid, 2-acrylamido-2-methylpropanesulfonic acid, styrenesulfonic acid, and propenylsulfonic acid.

24. The method according to any one of claims 17 to 23, wherein the polymerization reaction conditions include a temperature of 40 to 80°C and a time of 1 to 10 hours.

25. The method according to any one of claims 17 to 24, wherein the initiator is at least one selected from the group consisting of ascorbic acid, sodium formaldehyde sulfoxylate and sodium dithionite.

26. The method according to claim 25, wherein the content of the initiator is 0.1 to 1 weight percent of the total amount of the monomer mixture.

27. The polymerization reaction is carried out in the presence of an oxidizing agent and / or a chain transfer agent, The oxidizing agent is at least one selected from the group consisting of hydrogen peroxide, peracetic acid, ammonium persulfate, sodium persulfate, and potassium persulfate; And / or the process according to any one of claims 17 to 26, wherein the chain transfer agent is selected from thioglycolic acid and / or 3-mercaptopropionic acid.

28. Use of a polymer according to any one of claims 1 to 11 and a polycarboxylic cement dispersant according to any one of claims 12 to 16 in a cement slurry for cementing.

29. Use of a polymer according to any one of claims 1 to 11 or a polycarboxylic acid cement dispersant according to any one of claims 12 to 16 in a cement slurry for cementing in a high temperature well at 120°C or higher.

Citation Information

Patent Citations

  • Polycarboxylic acid water reducing agent

    CN103030334A

  • Copolymer,its production and additive comprising said copolymer and used for aqueous suspension

    JP1996283350A

  • Aqueous dispersion of fluororesin

    JP1997194538A

  • Use of polymers containing carboxyl groups and polyalkylene oxide ether-side chains as additives in mineral building materials

    JP2001507054A

  • Polymers containing carboxyl groups and polyalkylene ether side-chains as additives in mineral building materials

    US20020055559A1